(untitled) (College of Basic Education Research Journal, 2025)
Pre-Islamic poetry is considered an open welcoming space, and a great everlasting source for those who want to search for a topic. To find what you want and achieve what you aspire to. Bearing this in mind, I found myself searching for a topic that represents pre-Islamic era and trying to uncover something, though trivia, about secrets of this poetry, so I decided to navigate in (The Effect of Al-Badi’ on Structure of Poem in legacy of Al-Marqasheen), This paper includes an introduction and three chapters tackling Badi’ linguistically and terminologically. Components of poems of Al-Marqasheen, considered one of the most important elements in poetic formation. (Incipit, Conciseness, and closure) are among the most important elements followed in poems of pre-Islamic, that became a tradition followed by most succussing poets, and since Al-Marqasheen were one of founders of poem structure, it was necessary to consider elements that made up their poems, including incipit with its branches, transitions represented by elegant closure, main purpose of poem, good closure and the verses of wisdom that it contain.